Do Tourist Arrivals Contribute to the Stable Exchange Rate? Evidence from Indonesia - KUNCORO, Haryo (Journal of Environmental Management and Tourism, 2016)
The impact of exchange rate on tourism arrivals fluctuation has been well accepted in the frame work of demand function. However, literature on the influence of tourism arrivals on exchange rate stabilization revealed inconclusive. This paper attempts to analyze the economic importance of international tourism arrivals in Indonesia based on the question of whether tourism arrivals contribute to stabilize exchange rate. Estimation of monthly time series data for the period of 2004-13 presents that Hedrick-Prescott filtered cyclical components of tourism arrivals and exchange rate are co-integrated and bi-directional Granger-causality. The results of VAR present that cyclical characteristics of tourism arrivals are pro-cyclical to exchange rate implying that the increase in tourism arrivals induce the destination currency appreciation. These results indicate that tourism arrivals are sustainable inflow and have a big potency to absorb other external funding resources volatility in order to maintain adequate international reserve and therefore contribute to achieve the stable exchange rate. In such a case, improving the competitiveness of tourism sector should be an integral part of the exchange rate stabilization program.
Keywords: tourism; exchange rate; cyclicality; VAR; impulse response